Investigation of the effect of fly ash released from Kütahya thermal power plants by using remote sensing methods - Ayşe Dağlıyar; Fatma Melis Bayındır; Güzide Kalyoncu Ergüler (Bulletin of the Mineral Research and Exploration, 2021)
In order to determine the long-term effect of thermal power plants, the satellite images of Seyitömer and Tunçbilek Thermal Power Plants and their vicinities were analyzed by using the software of ERDAS IMAGINE v9.1 and PCI Geomatica 2017. The normalized difference vegetation index (NDVI) was determined by using red and near-infrared bands of Landsat satellite images, and areas containing vegetation were revealed in the images. In order to obtain the temporal change in the vegetation areas, the relevant image change detection analysis was applied and the one-year and thirty-year temporal change of vegetation cover is for r = 4 km, r = 12 km, r = 50 km. In the remote sensing mapping studies, it was determined that as the diameter of the assessment area increases, the dominant wind loses its effect, and geomorphological conditions are more prominent.